Meningkatkan Potensi Diri Menjadi Pemimpin Muda Yang Inspiratif Siswa SMA Negeri 1 Cabangbungin - Sarmin, Sarmin; Soedjatmoko, Soedjatmoko; Ririn Uke Saraswati; Ranuyoga Asryandi; Andrie Alamin; Muhammad Harun Ma’rifatullah6; Khoirunisa, Khoirunisa; Naidi Wizaya; Muhammad Maulana (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The Community Service (PKM) activity with the theme "Improving Self-Potential to Become an Inspiring Young Leader" is one of the implementations of the Tridharma of Higher Education program implemented by STIE Ekadharma Indonesia. The main objective of this activity is to provide a real contribution to the community, especially students, in efforts to develop self-potential and leadership from an early age. This activity targets grade XII IPS 4 students at SMA Negeri 1 Cabangbungin with a total of 33 participants. In this activity, participants are given a deep understanding of the importance of recognizing and developing their potential, including abilities, talents, interests, creativity, and superior character that can be the foundation for becoming an inspiring and competitive young leader. The material presented in the seminar is designed to equip participants with applicable strategies and insights, such as how to recognize their strengths, build self-confidence, and improve communication and leadership skills. The material delivery process is carried out interactively to encourage active student participation and create a fun and meaningful learning atmosphere. This activity also reflects the spirit of collaboration between higher education institutions and schools in preparing young people who are ready to face future challenges. Evaluation results indicate that this activity was highly effective, demonstrated by the high level of participant enthusiasm, a strong understanding of the material presented, and a positive response to the speakers. This activity is expected to inspire and motivate young people to continue developing themselves and making positive contributions, both within the school environment, on campus, and in the wider community.